Poroid hidradenoma on the nasal tip: a case report - WANG Xin; RONG Jian; LI Yaoyao; SONG Mei (Pifu-xingbing zhenliaoxue zazhi)
We report a case of poroid hidradenoma on the nasal tip. A 64-year-old man presented with a progressively enlarging subcutaneous mass on the nasal tip for two years. Dermatological examination revealed a palpable 1.2 cm×1.2 cm subcutaneous mass on the nasal tip, protruding approximately 0.3 cm above the skin surface. The mass had a smooth surface, soft texture, no cracking or scaling, and was well-defined from the surrounding tissue. Fluctuation was palpable, with no tenderness. The mass was mildly adherent to adjacent tissues and immobile. Ultrasound examination revealed a cystic subcutaneous lesion on the nasal tip, suggesting a sebaceous cyst. Skin histopathology showed tumor tissue consisted of numerous ducts and dense small glandular proliferation, with secretions in some glandular lumens, forming tumor-like nodules. The peripheral cells did not exhibit a palisading arrangement, and no notable retraction spaces were observed. The tumor cells were primarily small cuboidal cells with light pink-stained cytoplasm. The diagnosis was poroid hidroacanthoma. The tumor was completely excised under local anesthesia. Postoperative wound healing was successful, with no malignant transformation or recurrence during one year of follow-up.